pH Sensitive Hydrogels in Drug Delivery: Brief History, Properties, Swelling, and Release Mechanism, Material Selection and Applications - Rizwan, Muhammad (Polymers (Basel), 2017)
Improving the safety efficacy ratio of existing drugs is a current challenge to be addressed rather than the development of novel drugs which involve much expense and time. The efficacy of drugs is affected by a number of factors such as their low aqueous solubility, unequal absorption along the gastrointestinal (GI) tract, risk of degradation in the acidic milieu of the stomach, low permeation of the drugs in the upper GI tract, systematic side effects, etc. This review aims to enlighten readers on the role of pH sensitive hydrogels in drug delivery, their mechanism of action, swelling, and drug release as a function of pH change along the GI tract. The basis for the selection of materials, their structural features, physical and chemical properties, the presence of ionic pendant groups, and the influence of their pK(a) and pK(b) values on the ionization, consequent swelling, and targeted drug release are also highlighted.